An Industrial Floor Monitoring System Drone with Hazardous Gas and Smoke Detection - Che Hassan, Che Aqil Zulhazim; Yaacob, Megat Satria Zainuddin; Muhammad Rusydi Muhammad Razif; Muslim Abdullah Zaik; Nizzal Syafiq Bostaman (Progress in Engineering Application and Technology, 2024)
The "Industrial Floor Monitoring System Drone with Hazardous Gas and Smoke Detection" thesis presents a comprehensive study on the development and implementation of an autonomous drone system equipped with gas and smoke sensors for industrial safety and environmental monitoring. The project aims to address the limitations of traditional fixed sensors in providing comprehensive coverage of industrial facilities, particularly in detecting hazardous gas and smoke releases. The study encompasses a detailed exploration of the system’s design, integration of hardware and software components, and the utilization of IoT principles for real-time monitoring. The manuscript provides insights into the transformative journey of developing an innovative Industrial Floor Monitoring System Drone with Hazardous Gas and Smoke Detection, highlighting the project’s objectives, methodologies, and the seamless coordination between hardware components and data communication protocols.